Implementing adaptive management into a climate change adaptation strategy for a drowning New England salt marsh. (15th September 2020) - Perry, Danielle C.; Chaffee, Caitlin; Wigand, Cathleen; Thornber, Carol
Abstract: Due to climate change and other anthropogenic stressors, future conditions and impacts facing coastal habitats are unclear to coastal resource managers. Adaptive management strategies have become an important tactic to compensate for the unknown environmental conditions that coastal managers and restoration ecologists face. Adaptive management requires extensive planning and resources, which can act as barriers to achieve a successful project. These barriers also create challenges in incorporating adaptive management into climate change adaptation strategies. This case study describes and analyzes the Rhode Island Coastal Resources Management Council's approach to overcome these challenges to implement a successful adaptive management project to restore a drowning salt marsh using the climate change adaptation strategy, sediment enhancement, at Quonochontaug Pond in Charlestown, RI. Through effective communication and active stakeholder involvement, this project successfully incorporated interdisciplinary partner and stakeholder collaborations and developed an iterative learning strategy that highlights the adaptive management method. Highlights: We demonstrated the value of adaptive management in salt marsh restoration. Included planning and collaboration techniques for adaptive management success. We illustrated how effective communication and flexibility were vital for success.